Design of a nutrient solution supply device for a vertical aeroponic cultivation system - He, Yihan; Zhang, Xinghua; Wang, Ting; Tan, Xinyu; Liu, Shuguang (Frontiers in Plant Science, 2025)
Aeroponic cultivation systems provide precise environmental control for plant growth, effectively block the reproductive pathways of root diseases and pests, and facilitate efficient water resource recycling, thereby offering a scalable technical solution for intensive, high-yield, and sustainable agricultural production. Aiming to address the complex underground pipelines and excessive spray nozzles in fixed-pipeline nutrient solution supply systems of conventional vertical aeroponic cultivation, this study proposes a vertical aeroponic cultivation paradigm for large-scale production that can be applied to mobile nutrient solution supply modes. This study analyzes the structural components and operational workflow of the vertical aeroponic cultivation system, and the structural components, operational principles and technical specifications of the dedicated nutrient solution supply device. Transient dynamic analysis is conducted using ANSYS Workbench 2025 R1 (student) software, thereby yielding the equivalent stress/strain distributions on the body frame at 0.15 m/s, and on the spray bracket at 0.4 m/s. The simulation results demonstrate that both structures maintain stress within material limits and without significant concentration areas, with minimal strain levels meeting operational requirements. The Box-Behnken experimental design methodology is adopted to establish flow rate of the spray nozzles, moving speed of the spray nozzles, and vertical height from the test points on the legs of the trapezoidal cross-section of the cultivation bed to the ground as experimental factors, with nutrient solution coverage rate as evaluation indicator. The experimental results are analyzed using Design Expert 13.0 software to establish a regression model and conduct optimization analysis. The optimization results indicate that with a flow rate of 3 L/min for the spray nozzles and a moving speed of 0.38 m/s for the spray nozzles, the nutrient solution coverage rates on the legs of the trapezoidal cross-section of the cultivation bed reach >90% for both vertical height positions (0.1 m and 1.4 m from ground). This configuration ensures >90% nutrient solution coverage rate across the entire legs of the trapezoidal cross-section of the cultivation bed. Verification experiments confirm nutrient solution coverage rates at the respective test points are 90.33% and 91.52%, which is in accordance with the practical application requirements. This study will serve to diversify aeroponic production methodologies, expand development potential for commercial aeroponics, and provide valuable insights for technological dissemination.